2019
DOI: 10.1088/1361-665x/ab0ebe
|View full text |Cite
|
Sign up to set email alerts
|

Design, analysis and experimental investigation on the whole-spacecraft vibration isolation platform with magnetorheological dampers

Abstract: Satellites are subject to complex loads during launch, and harsh vibration environments often result in failures in launching satellites or damage to on-board instruments. A six-degree-offreedom conical vibration isolation platform with magnetorheological dampers has been proposed, which is highly integrated and used to partially replace the original connection device to improve the vibration environment. A mathematical model of the vibration isolation platform with rigid payload is established and natural fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The results show that compared with passive vibration isolation, MR semi-active vibration isolation can achieve better vibration reduction effect in a wide frequency range. Cheng et al (2019) conducted a similar study and showed that MR technology can reduce the satellite centroid vibration, while an interesting phenomenon was found that the acceleration transmissibility first decreases and then increases as the current increases. Nowadays, there are still very few public reports on MR whole-satellite vibration isolation research.…”
Section: Introductionmentioning
confidence: 98%
“…The results show that compared with passive vibration isolation, MR semi-active vibration isolation can achieve better vibration reduction effect in a wide frequency range. Cheng et al (2019) conducted a similar study and showed that MR technology can reduce the satellite centroid vibration, while an interesting phenomenon was found that the acceleration transmissibility first decreases and then increases as the current increases. Nowadays, there are still very few public reports on MR whole-satellite vibration isolation research.…”
Section: Introductionmentioning
confidence: 98%
“…Building a feedback control loop is a simple and efficient method that has been widely used in active vibration control (Cheng et al, 2019; Ma et al, 2022; Qian et al, 2022; Sharma et al, 2019). To reduce the main and super harmonic resonance of a flexible simple beam, Liu et al (2016) proposed an optimal delay feedback control method with a piezoelectric sensor and driver.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, image jitter is generated which could reduce the observation quality, even cause the observation task failure. Therefore, it is necessary to suppress the disturbances during positioning (Jian et al, 2018; Kamesh et al, 2012), especially the low-frequency vibrations and middle-high-frequency vibrations (Cheng et al, 2019; Wang et al, 2019). However, an awkward question is that even the scheme with series connection of a positioning platform and a vibration suppression platform could track the target and suppress the external disturbance well; the large size and mass, as well as the difficulty of collaborative control, all bring inconvenience to the on-orbit application.…”
Section: Introductionmentioning
confidence: 99%